Activation of phagocytic cells by Staphylococcus epidermidis biofilms: effects of extracellular matrix proteins and the bacterial stress protein GroEL on netosis and MRP-14 release. Issue 5 (23rd April 2016) - Dapunt, Ulrike; Gaida, Matthias M.; Meyle, Eva; Prior, Birgit; Hänsch, Gertrud M.
Abstract : The recognition and phagocytosis of free-swimming (planktonic) bacteria by polymorphonuclear neutrophils have been investigated in depth. However, less is known about the neutrophil response towards bacterial biofilms. Our previous work demonstrated that neutrophils recognize activating entities within the extracellular polymeric substance (EPS) of biofilms (the bacterial heat shock protein GroEL) and that this process does not require opsonization. Aim of this study was to evaluate the release of DNA by neutrophils in response to biofilms, as well as the release of the inflammatory cytokine MRP-14. Neutrophils were stimulated with Staphylococcus epidermidis biofilms, planktonic bacteria, extracted EPS and GroEL. Release of DNA and of MRP-14 was evaluated. Furthermore, tissue samples from patients suffering from biofilm infections were collected and evaluated by histology. MRP-14 concentration in blood samples was measured. We were able to show that biofilms, the EPS and GroEL induce DNA release. MRP-14 was only released after stimulation with EPS, not GroEL. Histology of tissue samples revealed MRP-14 positive cells in association with neutrophil infiltration and MRP-14 concentration was elevated in blood samples of patients suffering from biofilm infections. Our data demonstrate that neutrophil-activating entities are present in the EPS and that GroEL induces DNA release by neutrophils. Abstract : We were able to identify the bacterial heat shock protein GroEL as a neutrophil-activating entity within the biofilm matrix and for the first time demonstrate its effect on DNA release by neutrophils.